A PERCEPÇÃO SOBRE QUALIDADE DE VIDA DE CUIDADORES DE PESSOAS COM DEFICIÊNCIA: UM ESTUDO NA CIDADE DE RIO AZUL/PR - NÓS, REGIANE (2017)
This research aimed to present the perception of caregivers of people with disabilities about their quality of life. To do so, the profile of the study population was surveyed regarding demographic, health, occupational and socioeconomic aspects, and a descriptive analysis, with a qualitative approach, after the application of the WHOQOL questionnaire, enabled the knowledge and resignification of the relationships, capturing the universe of Perceptions, emotions and interpretations of caregivers. Twenty-one primary caregivers aged 23-61 years participated in this study, all of them female. People with disabilities are between the ages of 1 and 63 and attend the Association of Parents and Friends of the Exceptional (APAE) of Rio Azul / PR. Inclusion criteria were those individuals who provide assistance to individuals with disabilities for most of the day and who have been the primary caregiver for at least two months. And as exclusion criteria, people who have been the primary caregiver task for less than two months. For the collection of data, a Semistructured Interview by the researcher and the WHOqol Abridged Questionnaire prepared by the World Health Organization (WHO) were used as instruments. The Semistructured Interview is divided into four units, namely: 1) information related to the caregiver; 2) information related to the person with disability; 3) information related to the level of dependence of the disabled person; 4) family-related information (Appendix 1). The Whoqol Short Questionnaire consists of 26 questions, two general quality of life issues and the others representing each of the 24 facets that make up the original instrument, subdivided into four domains: Physical, Psychological, Social Relations and Environment. The importance of researching the quality of life of caregivers of people with disabilities lies in the fact that there is an overload from the routine of care they spend on each other, which can affect their physical, social and psychological health. Through this instrument, the quality of life of the caregivers is presented as Regular that points to the development of actions that contribute to its improvement.